STRATEGI KEBIJAKAN PENGEMBANGAN KAWASAN WISATA PANTAI MANGGAR KOTA BALIKPAPAN - Adi Wibowo; Adam Idris; Syahrani . (Jurnal Administrative Reform, 2017)
This research was using SWOT analysis to consider internal and external factors that influenced the tourist development in Manggar region. The result showed that there were a need for strategic policy which include increasing interest in sports especially sports like, jetsky, parasailing; next was to build networks with other available objects in Manggar Beach nearby such as breeding crocodiles house, Ambalat Beach and Lamaru Beach; together with tour and travel agents both in Indonesia and overseas; and then tighten the relationship between district and central governments; and last, create a website for Manggar Coastal Ressort.